Geometry of semi-nonholonomic hypercomplexes SNGr(1, 4, 5) in a four-dimensional projective space - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 2004)
In this article the problem of intrinsic normalizations of plane distributions in an four-dimensional projective space is considered.